2016
DOI: 10.7554/elife.21459
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genetic screens in human cells reveal new regulatory mechanisms in WNT signaling

Abstract: The comprehensive understanding of cellular signaling pathways remains a challenge due to multiple layers of regulation that may become evident only when the pathway is probed at different levels or critical nodes are eliminated. To discover regulatory mechanisms in canonical WNT signaling, we conducted a systematic forward genetic analysis through reporter-based screens in haploid human cells. Comparison of screens for negative, attenuating and positive regulators of WNT signaling, mediators of R-spondin-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
142
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(150 citation statements)
references
References 61 publications
(71 reference statements)
3
142
3
Order By: Relevance
“…Interestingly, LAPTM4B was shown to also regulate AP4 expression via its effects on c‐myc, resulting in a circular positive feedback loop. Although some research has shown that c‐myc works together with AP4 to regulate tumour pathogenesis (Xue et al ., ) or that AP4 regulates the Wnt signalling pathway (Lebensohn et al ., ), which also involves c‐myc, our report is the first to show that AP4 also regulates c‐myc by affecting LAPTM4B expression. As summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, LAPTM4B was shown to also regulate AP4 expression via its effects on c‐myc, resulting in a circular positive feedback loop. Although some research has shown that c‐myc works together with AP4 to regulate tumour pathogenesis (Xue et al ., ) or that AP4 regulates the Wnt signalling pathway (Lebensohn et al ., ), which also involves c‐myc, our report is the first to show that AP4 also regulates c‐myc by affecting LAPTM4B expression. As summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…WT HAP1-7TGP cells and genetically modified clonal derivatives were grown as described in the “Cell lines and growth conditions” section of Materials and methods in [3].…”
Section: Methodsmentioning
confidence: 99%
“…Our reporter-based screening platform has been described previously in detail (Lebensohn et al 2016;Pusapati, Kong, Patel, Krishnan, et al 2018) . NIH/3T3-CG cells were used because they respond to SHH in a concentration-dependent manner, carry stably integrated Cas9, and carry fluorescence-based, quantitative reporter of HH signaling (GLI-GFP) (Pusapati, Kong, Patel, Krishnan, et al 2018) .…”
Section: Crispr/cas9 Screen Targeting Lipid-related Genesmentioning
confidence: 99%